Awareness and prevalence of colorectal cancer risk factors among adult men in Kuala Selangor / Nurul-Athirah Mohd Azhari - Mohd Azhari, Nurul-Athirah (2016)
Globally, 1.4 million people were diagnosed with colorectal cancer and the number keep increasing each year. In Malaysia, colorectal cancer is the second most common cancer in men. A cross-sectional study was done among 58 adult men in Kuala Selangor using questionnaire to assess the level of awareness on colorectal cancer, to determine the prevalence of colorectal cancer risk factors and the major sources of information among adult men in Kuala Selangor. 36.2% of the adult men have low knowledge on colorectal cancer signs and symptoms, 10.3% of them knowing fully about the its signs and symptoms, 12% of them fully knowing about the risk factors of colorectal cancer and 13.8% of them do not know anything on its risk factors. The mean knowledge scores for signs and symptoms and risk factors is 2.74 ± 2.61 and 5.31 ± 3.70. The percentage of respondents having each of the colorectal cancer risk factors are 81% (physical inactivity), 48.3% (intake of vegetables and fruits), 43.1 % (being overweight and obese), 25.9% (smoking), 12.1% (family history) and 0% (alcohol intake). 25.2% of the respondents choose internet to obtain information on colorectal cancer. Hence, the adult men in Kuala Selangor have moderate level of awareness and colorectal cancer risk factors while internet is the most preferred sources of information.